Closing the Representation Gap in Micro and Small Enterprises: Some Critical Factors - Serrano, Melisa R.; Xhafa, Edlira (Philippine Journal of Labor and Industrial Relations; Vol 32 No 1&2 (2012): Philippine Journal of Labor and Industrial Relations, 2021)
Using data gathered through a survey, this paper identities critical factors and variables that may positively affect or influence collective representation of workers employed in micro and small enterprises (MSEs). These factors include: legislations on enforcement of formal employment contract, protection of job security, protection of the right to organize, and social security coverage; inclusion of skills training and upgrading among union services; using safety at work, grievances or problems at work, and income security or stability (e.g. minimum wage campaigns) as organizing themes; and establishment and/or strengthening of other forms or structures of organization to represent MSE workers. These factors will require creative and innovative union strategies, increased union visibility in the MSE sector, and a stronger role of unions in addressing issues and concerns of MSE workers.